Rediscovery of Hieracium nebrodense (Asteraceae), a little-known endemic of Sicily (Italy) - Di Gristina, Emilio; Gottschlich, Günter; Raimondo, Francesco M. (Phytotaxa, 2016)
Hieracium nebrodense Tineo ex Lojac., a little-known endemic of Sicily, has been rediscovered from the type locality after almost two centuries since its first and only collection made in 1830 in the Madonie Mountains (N Sicily). In line with the treatment in ‘Med-Checklist 2’, it is reclassified as a subspecies of H. schmidtii. A new combination is made and a detailed description and illustration are provided.